Fenomenologia e filosofia da secularidade moderna em Charles Taylor - Baptista, Raphael Faé (2015)
The ordinary meaning given to the secularization in the West, points to the purge of the religious view in public places and society, in which debates evidentiate themselves in a polarized clash between religious and scientific discourse, with the advantage of these last. Charles Taylor intends to demonstrate how timid and biased is this perspective. In the midst of the answer to the question “what has changed between belief and unbelief, in 500 years of Western civilization, from 1500 to 2000?”, he considers a set of redrafts and new meanings in old and new ways of thinking, acting and engage regarding to spirituality and its modes of social embeddedness. The aim here is to analyze the Taylorian reading key about secularization, the framework within which are going to be developed the current conditions of the belief and unbelief, with wide political, social, ethical, anthropological, and so forth, repercussions, on individuals and societies.